2008
DOI: 10.1111/j.1741-3737.2008.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Child Physical Placements Following Divorce: Descriptive Evidence From Wisconsin

Abstract: This study uses administrative data from the Wisconsin Court Record Database, linked with survey data collected from mothers (n= 789) and fathers (n= 690), to describe the living arrangements of children with sole mother and shared child physical placement following parental divorce. Contrary to prior research, results provide little evidence that children with shared placement progressively spend less time in their father’s care. We find that, over (approximately) 3 years following a divorce, their living arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
(27 reference statements)
2
22
0
Order By: Relevance
“…An additional problem associated with a lack of father-reported data is that prior research suggests that mothers’ and fathers’ reports differ in terms of both father-child contact and child support payment, such that fathers tend to report higher absolute levels of both (Schaeffer, Seltzer, & Dykema, 1998; Schaeffer, Seltzer, & Klawitter, 1991; Seltzer & Brandreth, 1995). Yet, despite differences in the absolute levels reported by mothers and fathers, in general, patterns found using each type of report tend to be similar (see, for example, Berger, Brown, Joung, Melli, & Wimer, 2008). Furthermore, Tach et al, (2010, footnote 3), compare mother and father reports of father-child contact approximately one year after a non-marital birth and find 94% agreement for whether the father had seen the child in the past year and 91% agreement for whether the father had seen the child at least once a month in the last year, providing some evidence that mother and father reports on such broad measures of visitation may not be overly inconsistent.…”
Section: Discussionmentioning
confidence: 94%
“…An additional problem associated with a lack of father-reported data is that prior research suggests that mothers’ and fathers’ reports differ in terms of both father-child contact and child support payment, such that fathers tend to report higher absolute levels of both (Schaeffer, Seltzer, & Dykema, 1998; Schaeffer, Seltzer, & Klawitter, 1991; Seltzer & Brandreth, 1995). Yet, despite differences in the absolute levels reported by mothers and fathers, in general, patterns found using each type of report tend to be similar (see, for example, Berger, Brown, Joung, Melli, & Wimer, 2008). Furthermore, Tach et al, (2010, footnote 3), compare mother and father reports of father-child contact approximately one year after a non-marital birth and find 94% agreement for whether the father had seen the child in the past year and 91% agreement for whether the father had seen the child at least once a month in the last year, providing some evidence that mother and father reports on such broad measures of visitation may not be overly inconsistent.…”
Section: Discussionmentioning
confidence: 94%
“…The issue of custody modification raises the question of the stability of JC arrangements over time, which was not considered as an outcome in this review. However, longitudinal studies in both the United States (L. M. Berger, Brown, Joung, Melli, & Wimer, 2008;Maccoby & Mnookin, 1992;Pearson & Thoennes, 1990) and Canada (Austin & Jaffe, 1994;Cloutier & Jacques, 1997) have consistently found that JC arrangements (especially JP) are less stable over time than SC arrangements. For example, found that 57% of JP, 31% of JL, and only 13% of SC arrangements changed in the period they examined.…”
Section: Downloaded By [Oregon State University] At 14:08 22 Decembermentioning
confidence: 95%
“…For example, children's living arrangements have implications for educational success; children living in households with married, biological parents in the home tend to be better off than children in any other living arrangement (Teachman, 2008). Stability is also a predictor of children's outcomes; changes in residence, school, and household family structure negatively impact children's outcomes following parental separation (Berger, Brown, Joung, Melli, & Wimer, 2008;Coleman & Glenn, 2010).…”
Section: Parental Divorcementioning
confidence: 98%